The influence of sintering temperature on mechanical and microstructural properties of bovine hydroxyapatite - (:unkn) unknown (TRANS TECH PUBLICATIONS LTD, 2005)
The influence of sintering temperature on densification, microstructure and the mechanical properties of bovine hydroxyapatite (BHA), produced by a calcination method, was investigated. Densification and mechanical properties increased over increasing sintering temperature in the range between 1000 degrees and 1300 degrees C, and there are evidences of optimum sintering temperature at 1200 degrees C. The measured mechanical properties indicate sintered BHA-bodies as interesting biomaterials for further investigation in biomedical applications.
Keywords: bovine hydroxyapatite; mechanical properties; microstructure; sintering; REINFORCED HYDROXYAPATITE; BONE; DENTIN